Jenis dan karakteristik konten media sosial instansi pemerintah dan keterikatan pengguna - Sanda Aditiya Arsandi; Riki Andi Saputro; Nyarwi Ahmad (Faculty of Communications Science, Dr. Soetomo University, 2024)
The growing number of social media users has become a momentum for government agencies to optimise their social media accounts. This study aims to analyse types and characteristics of the government agency’s social media contents and users engagement regarding these contents. Extracting the contents posted in the Indonesian Instagram account using the quantitative and thematic content analyses, different test was carried out to determine whether there was a significant difference in user engagement. This article reveals the following findings. Materials posted by DGT’s Instagram consist of not merely the government agencies in Indonesia. They could adopt this model when formulating workable social media content strategies to educate, attract and mobilise social media users to achieve their goals.